Augmented Reality Introduction to Animals of the Archipelago to Grow the Nation's Love for Children - Anis Susila Abadi; Pipit Febriana Dewi; Bambang Robi'in (Jurusan Teknik Informatika, 2022)
Purpose: Produce Augmented Reality applications as a medium for introducing Indonesian animals to foster the nation's love for children.Design/methodology/approach: AR applications are built using markers. AR application development uses the MDLC method, which consists of six stages, namely concept, design, material collection, manufacture, testing, and distribution.Findings/result: This research resulted in the application of Augmented Reality Animal Recognition. The results of the tests that have been carried out using the similarity test of 92% for testing the similarity of 3D objects on animals. SEQ testing with an average result of 91.18 on a scale of 10, so it can be concluded that the application has met the needs of users.Originality/value/state of the art: The development of this application focuses on AR applications with models of Indonesian animals and explanations of the characteristics of these animals.